FAKTOR-FAKTOR YANG MEMPENGARUHI TERJADINYA WASTING PADA ANAK BALITA DI WILAYAH KERJA PUSKESMAS BANDAR KABUPATEN BENER MERIAH - Fitriani, Desi; HS, Nurlaely; Yusran, Mawadhah; Arami, Nova (Jurnal Ilmiah Cerebral Medika, 2024)
ABSTRACT Wasting is a condition where a child is underweight as a result of not meeting the need for a balanced nutritional intake. Wasting can disrupt a child's physical growth and intelligence, even worse, it can result in child death. The aim of this research is to find out and analyze the factors that influence the occurrence of wasting in toddlers. This type of research uses quantitative research using cross sectional research. The sample in this study amounted to 37 respondents. The instrument used was a questionnaire. This research was conducted at the Bandar Health Center, Bener Meriah Regency. Data analysis was carried out univariately and bivariately with the chi-square test (a=0.05). The results of the research show the distribution of factors that influence wasting, namely maternal parenting with a value (p-value=0.022), history of infectious diseases with a value (p-value=0.001), economic status with a value (p-value=0.032), education mother with value (p-value=0.042), mother's occupation with value (p-value=0.230) age with value (p-value=0.020), parity with value (p-value=0.022), knowledge with value (p- value=0.032). Factors that influence wasting are the mother's parenting style, history of infectious diseases, economic status, mother's education, age, parity and mother's knowledge. Meanwhile, the factor that did not influence wasting in this study was the mother's job. Keywords : Wasting, Mother's Parenting Style, History of Illness, Economic Status, Mother's Education, Age, Parity, Mother's Knowledge